Foundations and practice of security : 10th International Symposium, FPS 2017, Nancy, France, October 23-25, 2017, Revised selected papers /: 10th International Symposium, FPS 2017, Nancy, France, October 23-25, 2017, Revised selected papers. (2018) - Unknown
No abstract available